2021
DOI: 10.1097/mcg.0000000000001646
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Negatively Impacts Gluten Avoidance and Nutritional Intake in Patients With Celiac Disease

Abstract: Background: Food insecurity is a major public health challenge. For patients with celiac disease (CeD), food insecurity may be particularly detrimental as it threatens the cornerstone of their treatment: adoption of a gluten-free diet (GFD). We aimed to characterize the prevalence of food insecurity in patients with CeD and evaluate its impact on GFD adoption and nutritional intake. Methods: We analyzed data from patients with CeD participating in the US National Health and Nutrition Examination Survey (NHAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…The prevalence of food insecurity in our study was similar to previous reported data from the United States among individuals with CeD (23, 24), and higher than previous reported data among a general sample of adults with a relatively low socioeconomic position living in the Netherlands (33). Our findings confirm the established correlation between food insecurity, lower income and educational level(34).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The prevalence of food insecurity in our study was similar to previous reported data from the United States among individuals with CeD (23, 24), and higher than previous reported data among a general sample of adults with a relatively low socioeconomic position living in the Netherlands (33). Our findings confirm the established correlation between food insecurity, lower income and educational level(34).…”
Section: Discussionsupporting
confidence: 90%
“…A recent review of national survey data collected in the United States between 2008 and 2014, revealed the negative effects of food insecurity in individuals with CeD. Food insecurity was found to be significantly associated with decreased adherence to a gluten-free diet, as well as a reduced intake of essential nutrients, such as protein, various vitamins and several minerals (24). Notably, individuals with CeD already are at higher risk of certain vitamin and mineral deficiencies due to malabsorption, making them particularly vulnerable to the adverse effects of food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Etiologies of food insecurity include poverty, unemployment, low‐income, lack of affordable housing, systemic racism and racial discrimination, chronic health conditions, expensive dietary treatments, and lack of access to healthcare 9 . Within pediatric gastroenterology clinics, prior studies reported rates of food insecurity ranging from 13% to 17% 10,11 . Caregiver responses from our survey indicated that 10%−15% of families recalled being asked about food insecurity by a healthcare team member despite the numerous studies showing the impact that it may have on disease management.…”
Section: Discussionmentioning
confidence: 67%
“…9 Within pediatric gastroenterology clinics, prior studies reported rates of food insecurity ranging from 13% to 17%. 10,11 Caregiver responses from our survey indicated that 10%−15% of families recalled being asked about food insecurity by a healthcare team member despite the numerous studies showing the impact that it may have on disease management. For example, a study of patients with celiac disease demonstrated that one in six patients faced food insecurity, and less than one-quarter of those patients adhered to a gluten-free diet.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation